THIRD AND FOURTH IPSILATERAL AND CONTRALATERAL PRIMARY BREAST CANCER IN A COHORT OF WOMEN TREATED FROM 2000 TO 2015 AT AC CAMARGO CANCER CENTER - Rocha, Ariane Silva da; Curado, Maria Paula; Fernandes, Gisele Aparecida (Mastology, 2021)
This study aims to describe the clinical and pathological characteristics in women with breast cancer with three or four ipsilateral and contralateral malignant tumors. The second primary malignant neoplasm of the breast is a condition in which the frequency of occurrence is around 50%, mainly in young women. The occurrence of the third and fourth neoplasms is rare, between 0.73% and 11.7%. This is a retrospective cohort study of women with breast cancer from 2000 to 2015. We identified 375 women with second primary breast tumor, of which 6 (1.6%) had three and four new primary breast cancer. Of the six cases with three and four neoplasms, three cases occurred in the QIE (lower left quadrant), overlapping lesion in two cases, and two cases in the QSE (upper left quadrant). Zero clinical and pathological staging was observed in two cases, I in two cases, IIA in two cases, and IA in one case, invasive lobular carcinoma in four cases, and invasive ductal carcinoma in three cases. The molecular subtype luminal occurred in four cases, HER2 overexpressed in three cases, estrogen receptor and HER2 were negative in three cases, and progesterone positive in three cases. The time of diagnosis between the first, third, and fourth tumor ranges from 2 to 72 months. Therefore, more studies are needed on the third and fourth malignant breast tumors as it is a rare entity in patients whose genetic and molecular characteristics are poorly known.